(untitled) (Economics and region, 2025)
During wartime, brands transcend their traditional market roles and become active agents of social, economic, and humanitarian transformation. The full-scale war in Ukraine has fundamentally shifted public expectations toward businesses, demanding not only the provision of quality products and services, but also genuine social responsibility, support for the military, involvement in humanitarian initiatives, job preservation, and ethical communication. In this context, corporate social responsibility evolves beyond conventional PR or philanthropy into a strategic framework for long-term brand positioning, rooted in ethical dilemmas and heightened societal sensitivity. This article explores the role of brand social responsibility as a vital component of strategic brand management during military conflict. It synthesizes theoretical foundations developed by H. Bowen, A. Carroll, M. Porter, and P. Kotler, and contextualizes them within the realities of wartime Ukraine. Based on analysis of international and domestic case studies − including Airbnb, Uber, Silpo, Nova Poshta, ATB, and Rozetka − the article outlines successful strategies of CSR implementation, emphasizing the importance of transparency, consistency, and authentic engagement. Furthermore, the paper highlights key ethical challenges brands face in wartime: decisions to cut ties with aggressor-state partners, balancing publicity with sincere aid, and prioritizing moral values over short-term profits. The article identifies both effective and unsuccessful examples of brand responses, illustrating the reputational risks of inaction or opportunism. In conclusion, CSR in wartime must become an integrated, systemic element of strategic brand management − not an occasional reaction. Brands that respond ethically, act promptly, and align with societal needs will not only maintain resilience but also contribute to national recovery and sustainable development.